Implementasi Bussiness Intelligent dalam e-Tourism Berbasis Big Data - chandra eko wahyudi utomo (Journal of Tourism and Creativity, 2019)
Abstract The use of information technology that is integrated with work processes in an organization has become an absolute necessity. The availability of complete, correct and accurate data and information has become a basic requirement for the survival of an organization. Business Intelligence (BI) is a form of implementation that is able to answer the above needs. BI has been widely used by organizations in managing data and information to support decision making. BI is usually associated with efforts to maximize the performance of an organization. Business Intelligence System is a term that is generally used for the type of application or technology used to assist BI activities, such as collecting data, providing access, and analyzing data and information about company performance. Along with the rapid online-based information systems including e-tourism, creating a huge data explosion on the internet (bigdata). The very high growth of tourism data on the internet can be utilized for the needs of the tourism industry and research needs in the field of tourism. Keywords: intelligent business, e-tourism, big data